Isolasi, Purifikasi dan Immunogenitas Protein Outer Membran Vibrio Alginolyticus pada Ikan Kerapu Macan (Epinephelus fuscoguttatus) - Desrina Desrina; Arief Taslihan; Ambariyanto Ambariyanto; Ervia Yudiati; Yulius Docang Casessar; Raden Bagus Sugio Sumanta; Triyanto Triyanto; Hotnida Junita Situmeang; Langkah Sembiring (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The main objectives of this research were to isolate, purify and determine the immunogenicity of the outer membrane protein of V. alginolyticus. The outer membrane protein was isolated by sonication, sodium dodecyl sulphate-polyacrylamide agarose gel electrophoresis (SDS-PAGE) and purified by electroelusion method. Four outer membrane proteins were obtained: namely 32.0; 37.83; 64.13 and 73.43 kDa. Its immunogenicity in grouper Epinephelus fuscoguttatus was compared to that of bacterin of the same isolate. The immunogenicity test was conducted by intra peritoneal injection method. Each protein was dissolved in sterile Phospate Buffer Saline (PBS) and Freund’s Complete Adjuvant (FCA) (1:1) and injected 5 µg/ fish (fish weight 10-15 g). Bacterin (106, 107 and 108 cells/ml) was prepared in the same manner and injected at dosage of 0,2 ml/fish. Control fish were injected with 0.2 ml sterile PBS (pH 7.2). Booster was done a week later by injecting protein or bacterin with the Freund’s Incomplete Adjuvant (FIA). The agglutination test of antibody produced recognized cell surface protein of the whole cell of V. alginolyticus. Outer membrane protein 73.43 kDa was more immunogenic than the rest of proteins and bacterin, based on agglutinating antibodi titer.